Influence of gestational diabetes mellitus on lipid signatures in breast milk and association with fetal physical development - Zhong, Hong; Zhang, Jiahua; Xia, Jiaai; Zhu, Yuting; Chen, Chen; Shan, Chunjian; Cui, Xianwei (Frontiers in Nutrition, 2022)
GDM commonly leads to adverse pregnancy outcomes and long-term metabolic complications in offspring. Breastfeeding has been shown to rewrite the fetal “metabolic programming” resulting from maternal diabetes and finally lead to a lower risk of future metabolic disease. Lipids in breast milk act like hormones to promote infant growth and development, but there is minimal information invested thus far in constitution changes of lipids in breast milk, especially in the context of GDM. In the present study, we performed a lipidomics analysis to compare the lipid composition in breast milk collected from women with or without GDM. We further revealed the correlations of dysregulated lipids in breast milk with maternal glucose and infant physical development. A total of 833 lipid species from 15 classes were identified, 60 of which were found to be significantly altered in response to the high glucose, suggesting a remarkable lipid profiling change in breast milk induced by GDM. Our results showed significant associations between dysregulated lipids (e.g., neutral lipids, phospholipids, sphingolipids) and maternal glucose. Furthermore, correction analysis demonstrated that GDM related lipids were also associated with indicators of infant physical development, including body weight, length and head circumference. These findings may help to understand the protective effects of breastfeeding especially during GDM pregnancy.